Sustainable Consumption in the Behavior of Young Consumers - Wyrwa, Joanna; Barska, Anetta; Jędrzejczak-Gas, Janina; Kononowicz, Krzysztof (European Journal of Sustainable Development, 2023)
The aim of the article is to characterize the attitude of young consumers towards the concept of sustainable consumption in the area of food consumption, which is manifested, among others, in the declared engagement in sustainable behaviors both in the market as well as in households. The research was conducted using the CAWI method on a sample of Polish consumers from the Lubuskie region. The article consists of two parts. The first part explores the problems of sustainable consumption. The second part presents the results of research on consumer attitudes towards the concept of sustainable consumption in the area of food consumption. Particular attention was paid to the awareness of the implications of consumer behavior in the process of satisfying food needs. Behaviors, attitudes and beliefs of consumers related to sustainable consumption were characterized, and an attempt was subsequently made to determine the extent of the gap existing between behaviors and attitudes. The conducted survey research constituted an attempt at highlighting certain consumption problems among young people, to have them share their views on the different issues of sustainable consumption, as well as to emphasize the importance of various factors in shaping sustainable food consumption patterns. The article certainly is not an exhaustive examination of all the problems areas of sustainable consumption, but it should make these more easily identifiable all while stressing the real role and importance of sustainable behaviors among young consumers in the modern economy. Keywords: sustainable consumption, sustainable development, young consumer.